Encapsulation of indocyanine green into cell membrane capsules for photothermal cancer therapy. (1st October 2016) - Sheng, Guoping; Chen, Ying; Han, Lijie; Huang, Yong; Liu, Xiaoli; Li, Lanjuan; Mao, Zhengwei
Graphical abstract: Encapsulation of ICG into cell membrane capsules (CMCs) significantly slows down the body clearance of photosensitizer and results in better photothermal effect in vivo . Abstract: Although indocyanine green (ICG) has promising applications in photothermal therapy (PPT) because of its low toxicity and high efficiency in inducing heat and singlet oxygen formation in response to near-infrared light with a wavelength of approximately 800 nm, its clinical application has been restricted because of its rapid body clearance and poor water stability. Therefore, cell membrane capsules (CMCs) derived from mammalian cells were used to encapsulate negatively charged ICG by temporarily permeating the plasma membrane and resealing using positively charged doxorubicin hydrochloride (DOX). The resulting CMCs@DOX/ICG exhibited a spherical shape, with a diameter of approximately 800 nm. The DOX and ICG encapsulation was confirmed by the UV–vis spectrum; a very small amount of DOX (0.8 μg) and a very high amount of ICG (∼110 μg) were encapsulated in 200 μg CMCs. Encapsulation in the CMCs leads to sustained release of ICG, especially in the presence of positively charged DOX. The temperature enhancement and generation of ROS by ICG encapsulated in CMCs were confirmed upon laser irradiation in vitro, leading to cell death. CMCs@DOX/ICG also can significantly enhance the retention of ICG in a tumor after intratumoral injection in vivo . As a result, combination treatment with CMCs@DOX/ICG and laser irradiation demonstrated much better anticancer efficacy than that of free DOX/ICG and CMCs@ICG. The encapsulation of ICG into CMCs, especially with the assistance of DOX, significantly slows down the body clearance of ICG, with a retained PPT effect against tumors, an important step forward in the practical application of ICG in cancer therapy. Statement of Significance: In this study, cell membrane capsules (CMCs) derived from mammalian cells were used to encapsulate negatively charged indocyanine green (ICG) by temporarily permeating the plasma membrane and resealing, in the presence of positively charged doxorubicin hydrochloride (DOX). The resulting CMCs@DOX/ICG exhibited a spherical shape, with a diameter of approximately 800 nm. Encapsulation in the CMCs leads to sustained release of ICG and thus slower clearance inside body, especially in the presence of positively charged DOX. The system provides a better photothermal effect against tumors, an important step forward in the practical application of ICG in cancer therapy.